Histone deacetylase 4 associates with extracellular signal-regulated kinases 1 and 2, and its cellular localization is regulated by oncogenic Ras - Zhou, Xianbo (The National Academy of Sciences, 2000)
Histone deacetylase 4 (HDAC4) is a member of a family of enzymes that catalyze the removal of acetyl groups from core histones, resulting in a compact chromatin structure that is generally associated with repressed gene transcription. Protein phosphorylation has been implicated in the regulation of the corepressor activity of the deacetylase. Here we report that serine/threonine kinases are found in association with HDAC4 and phosphorylate HDAC4 in vitro, and HDAC4 is phosphorylated in cells. The extracellular signal-regulated kinases 1 and 2 (ERK1/2), also known as p44(MAPK) and p42(MAPK), respectively, are two of the kinases associated with HDAC4. ERK1/2 are components of the Ras–mitogen-activated protein kinase (MAPK) signal transduction pathway. Activation of the Ras–MAPK pathway by expression of oncogenic Ras or constitutively active MAPK/ERK kinase 1 results in an increased percentage of cells (from ≈10% to ≈70%) that express HDAC4 in the nucleus in C2C12 myoblast cells. In cells transfected with oncogenic Ras, nuclear HDAC4 is associated with kinase activity. Our results provide evidence that protein kinase activity is present in a protein complex with HDAC4 and directly links the Ras–MAPK signal transduction pathway to a mechanism for chromatin remodeling (i.e., histone deacetylation).